Natural Resources, Conflict, and Sustainable Development : Lessons from the Niger Delta. - Ukaga, Okechukwu (Routledge African studies., 2012)
The Niger Delta Region has in the past two decades experienced protracted violent conflicts. At the roots of these violent conflicts are the genuine quests of the people for sustainable development that is based on social justice, equity, fairness and environmental protection. Although richly endowed, the region is hopelessly poor. This paradox of poverty in the midst of plenty has been attributed to a myriad of factors ranging from Nigeria, s centralized federalism, to ethno-regional domination, corruption, poor governance, and oil-related environmental degradation. Development in the Niger De.